PENERAPAN DESAIN KEMASAN HASIL PENELITIAN DALAM MEMPERKUAT IDENTITAS DAN DAYA SAING UMKM KERIPIK TEMPE - Sari, Novi; Prastiwinarti, Wiwi; Amir, Anneke; Fatah, Abdillah; Rizwan (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to improve the competitiveness of both MSMEs in the global market through the implementation of packaging redesign and increased knowledge through training. The implementation methods include the implementation of design results obtained from research and assistance through training. The packaging redesign process was developed using the Kansei Engineering method to translate consumer perceptions into effective design elements, involving respondents and expert panelists. The training material covers the strategic functions of packaging design, material selection, and sales strategies. The main outcome of this program is functional, attractive, and optimally protective printed packaging products, which directly address the issue of damage and increase sales value. The community service program for tempeh chip MSMEs in Kebayoran Baru has successfully increased understanding of packaging design. This is evident from the increase in participants' knowledge scores from an average of 4.1 (initial test) to above 4.7 (final test). The success of this outreach and practice program provides a strong foundation, where the application of new packaging design results is expected to effectively increase the competitiveness of MSME products.